2017
DOI: 10.5901/mjss.2017.v8n1p78
|View full text |Cite
|
Sign up to set email alerts
|

Managerial Ownership, Board of Directors, Equity-based Compensation and Firm Performance: A Comparative Study between France and the United States

Abstract: The aim of this comparative study between the French and American markets, characterized by a different ownership

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…One possible explanation for this result could be as follows. According to our literature review, managerial and institutional ownership influence greatly the firm financial performance (Kim et al , 2013; Apriada and Suardhika, 2016; Bouras and Gallali, 2017; Alfinur, 2016; Apriada and Suardhika, 2016; Pertiwi and Hermanto, 2017; Sukmawardini and Ardiansari, 2018). On the other side, our results report that managerial ownership and institutional ownership impact CSR engagement.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One possible explanation for this result could be as follows. According to our literature review, managerial and institutional ownership influence greatly the firm financial performance (Kim et al , 2013; Apriada and Suardhika, 2016; Bouras and Gallali, 2017; Alfinur, 2016; Apriada and Suardhika, 2016; Pertiwi and Hermanto, 2017; Sukmawardini and Ardiansari, 2018). On the other side, our results report that managerial ownership and institutional ownership impact CSR engagement.…”
Section: Resultsmentioning
confidence: 99%
“…In a similar vein, DeAngelo and DeAngelo (1985) suggested that high managerial shareholding could solve the problem of asymmetric information related to investments. Therefore, based on this assumption, there is a positive relationship between the proportion of shares held by managers and firm performance (Bouras and Gallali, 2017). Similarly, the results of research conducted by Apriada and Suardhika (2016) reported that managerial ownership affects positively the firm value.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…Against this background, it suggests that the higher the director's ownership in the firm, the higher the firm's financial performance will be [45]. The convergence of interest hypothesis presented by DeAngelo and DeAngelo [46] and some past studies also assumes a positive association between managerial ownership and firm's financial performance of firms [43,[47][48][49]. Hence, in the context of the above discussion, the following hypotheses are designed.…”
Section: The Moderating Role Of Managerial Ownership On the Link Betwmentioning
confidence: 94%
“…At this point, the interest of managers converges with the interest of the firm, and in the process, the firm's value gets better. The past studies of [42,43] proxied managerial ownership through the director's ownership. In Malaysia [44] the director's ownership was also as a proxy for measuring managerial ownership.…”
Section: The Moderating Role Of Managerial Ownership On the Link Betwmentioning
confidence: 99%
“…Some scholars argue that centralization can drive firm performance while others hold the opposite view [4] . Only a few scholars find a nonlinear relationship between centralized management and firm performance [5]. We believe that the reason why views vary is that most studies have ignored the importance of the firm size effect and only have used it as a control variable.…”
Section: Introductionmentioning
confidence: 99%